EXPERIMENTAL STUDIES AND NUMERICAL ANALYSIS FOR THE DEFORMATIONSTRENGTH CHARACTERISTICS OF RAMMED MICRO-PILES WITH A BROADENED AGGREGATE BASE - V. S. Alekhin; N. V. Kupchikova (Вестник Дагестанского государственного технического университета: Технические науки, 2017)
Objectives. Experimental and theoretical determination of dependencies of strength characteristics of bored micropiles with a pedestal formed by rammed rubble on: casing diameter, fraction, and volume of crushed stone for collapsing macroporous clays. Method. Laboratory and field experiments were carried out; numerical calculations in two-dimensional and threedimensional arrangement for the determination of strain-stress analysis of the foundation using a MIDAS GTS_NX software system, implementing the finite element method and developed for complex geotechnical problems; some recommendations for implementation are provided. Results The dependence of the load-bearing capacity of bored micropiles on a broadened base of rammed aggregate with vertical loading is determined. At the maximum broadening diameter of 3.5 of the micropiles shaft the load-bearing capacity of the subsoil is increased by between 1.8 and 6 times compared with micropiles without broadening depending on the diameter of the pile shaft. During the experimental and numerical studies of the dependencies of deformation-strength parameters of the deep foundation works consisting of a bored micropile with a broadened base, namely the pile diameter, aggregate particle size and volume, seal diameter of the subsoil soil half-space, as well as the development of the theory of formation of the end broadening geometry of rammed aggregate in the form of an ellipsoid of revolution were established. Conclusion The full-scale measurements of the broadening of bored micropiles showed that their shape is close to an ellipsoid of revolution, and the ratio of semi-axes is directly dependent on the characteristics of soil and gravel volume, which was taken into account in the construction of the finite element model in the numerical simulation experiment.The results of numerical studies of the bored micropile loading with broadened base on the MIDAS GTS show good agreement with the results of the field test, consisting of a difference of between 2 and 15%.